Construcción de la identidad con hinchas bogotanos que conforman la barra del disturbio rojo. (2020)
This research work is born from the idea of ​​understanding the different forms of identity construction in a certain group of fans, in order to deepen the ways in which an explanation of why one is a soccer fan is given: what makes it so special, what are those meanings that denote the practices that lead to building identity from the idea of ​​being a fan. Given that, in the first instance, an exhaustive review of authors who have addressed the subject is carried out, in order to give an explanation of the possible causes that lead to being reflected in ideas that are born from a football club. In accordance with this, a review is made of the history of the club selected for the investigation in this case América de Cali, with Bogota fans who make up the Disturbio Rojo Bogotá bar; It also explains which of the connotations that identify the Club are most noticeable to them and what makes them unique and special. Subsequently, it is complemented by ethnographic work, from a series of visits to the El Campin stadium, when it came to play with the capital teams. The results obtained after the investigation are also exposed, complemented by the description of what was observed, to finally reconsider the various ways of constructing identity and how it becomes a forging element of citizen training. Keywords Identity, Fans, Club, Territory, Emblems, Colors, Citizenship.